FIRST OCCURRENCE OF TEMNOCEPHALA CURVICIRRI AMATO AND AMATO, 2005 IN BELOSTOMA SP. (HEMIPTERA, BELOSTOMATIDAE) IN SANTA CATARINA, SOUTHERN BRAZIL - Marinho de Quadros, Rosiléia (2022)
A single specimen of Belostoma sp., a hemipteran belostomatid insect from the interior of the city of Bocaina do Sul, state of Santa Catarina, was brought to the Laboratory of Parasitology and Zoology of Universidade do Planalto Catarinense (UNIPLAC), Brazil. The hemipteran examined was infested with two specimens of Temnocephala curvicirri Amato & Amato, 2005, found on the ventral surface of Belostoma sp. between the second and third locomotor pair of the insect. Externally, the light colored helminth is characterized by the presence of an adhesive disk with a fingerlike appearance. The temnocephalid was identified by its extremely long and curved cirrus. This is the first report of the presence of T. curvicirri in Santa Catarina.